2020
DOI: 10.1038/s42003-020-01391-5
|View full text |Cite
|
Sign up to set email alerts
|

Tet2 at the interface between cancer and immunity

Abstract: Keeping a balance between DNA methylation and demethylation balance is central for mammalian development and cell function, particularly in the hematopoietic system. In various mammalian cells, Tet methylcytosine dioxygenase 2 (Tet2) catalyzes oxygen transfer to a methyl group of 5-methylcytosine (5mC), yielding 5-hydroxymethylcytocine (5hmC). Tet2 mutations drive tumorigenesis in several blood cancers as well as in solid cancers. Here I discuss recent studies that elucidate mechanisms and biological consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 59 publications
1
44
0
Order By: Relevance
“…Loss of function TET2 mutations are found in a wide variety of blood cancers in addition to clonal hematopoiesis. 15 Deletion of Tet2 in the blood system resulted in myeloid cancer development after long latencies in mice, confirming its role as a tumor suppressor. 5 , 15 In solid cancers, previous analyses of melanoma 7 and liver cancer 8 models indicated that Tet2 ‐deficient MDSC modulate cancer progression by altering T cell‐mediated immunity, although they played opposite roles in T‐cell recruitment in each model.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Loss of function TET2 mutations are found in a wide variety of blood cancers in addition to clonal hematopoiesis. 15 Deletion of Tet2 in the blood system resulted in myeloid cancer development after long latencies in mice, confirming its role as a tumor suppressor. 5 , 15 In solid cancers, previous analyses of melanoma 7 and liver cancer 8 models indicated that Tet2 ‐deficient MDSC modulate cancer progression by altering T cell‐mediated immunity, although they played opposite roles in T‐cell recruitment in each model.…”
Section: Discussionmentioning
confidence: 91%
“… 15 Deletion of Tet2 in the blood system resulted in myeloid cancer development after long latencies in mice, confirming its role as a tumor suppressor. 5 , 15 In solid cancers, previous analyses of melanoma 7 and liver cancer 8 models indicated that Tet2 ‐deficient MDSC modulate cancer progression by altering T cell‐mediated immunity, although they played opposite roles in T‐cell recruitment in each model. Intriguingly, our findings in a lung cancer model strongly suggest that Tet2 ‐deficient myeloid cells alter activity of a vascular niche for tumor cells rather than directly altering T‐cell mediated immunity.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, loss-of-function mutation of TET2 results in a predominance of 5mC in DNA [ 134 ]. The accumulation of 5mC can promote B-cell development and function resulting in activation of innate immune systems, as well as the disruption of DNA methylation homeostasis [ 136 , 137 ]. Despite there being controversies in the functional impact of TET2 mutations in MDS, it remains as an important epigenetic enzyme [ 10 , 134 , 135 ].…”
Section: Molecular Pathogenesis Of Mdsmentioning
confidence: 99%
“…DNA 5mC methylation is the classic epigenetic process, which is controlled by “writers” (DNA methyltransferases), “erasers” (DNA methyltransferases), and “readers” ( Ito et al, 2011 ; Du et al, 2015 ; Lio et al, 2020 ). With the discovery of 5mC regulators, recent studies suggested that DNA cytosine modifications may act as epigenetic markers in tumorigenesis ( Wu and Zhang, 2010 ; Cavalcante et al, 2020 ; Jiang, 2020 ; Mo et al, 2020 ) and can regulate tumor microenvironment (TME) infiltrating cells ( Chen et al, 2020 ; Zhao et al, 2021 ; Onodera et al, 2021 ). However, the comprehensive roles of TME cell infiltration directed by 5mC regulators in NSCLC remain unclear.…”
Section: Introductionmentioning
confidence: 99%